Effort-reward imbalance at work: the role of job satisfaction. Issue 2 (5th March 2018) - Devonish, Dwayne
Abstract : Purpose: The purpose of this paper is to examine the mediating role of job satisfaction in the relationship between effort-reward imbalance (ERI) and burnout, turnover intentions, and mental health. Design/methodology/approach: Based on a sample of 323 full-time employees in the small developing country in the Caribbean, this survey study tested a mediation model with job satisfaction depicting the relationship between ERI and various outcome variables. The model was compared to a partial mediation model. Findings: The structural equation modelling (SEM) results revealed that the partial mediating model was superior to the full mediation model, suggesting that job satisfaction plays only a partial role in mediating the relationships between ERI and burnout, turnover intentions, and mental health. Research limitations/implications: The study presents a cross-sectional approach to model testing but the study controlled for CMV statistically using the common latent factor approach within latent SEM procedures. Practical implications: Organisations should ensure that employees' efforts are appropriately and fairly rewarded as a means of reducing negative ERIs which can have adverse consequences on the physical and mental health of employees. Originality/value: Using latent SEM procedures and statistical controls for CMV, the study examined job satisfaction as a potential mediator in a popular stressor-strain model.